Penggunaan Limbah Batu Cadas Sebagai Agregat Kasar Dalam Campuran Beton - I Gede Oka Darmayasa (Program Studi Teknik Lingkungan Unmas Denpasar, 2023)
The current high development activity causes the need for building materials to continue to increase, especially concrete-forming aggregates. To overcome this problem, alternative materials are needed as substitute aggregates in the concrete mix. This study used rock waste as an ingredient in the concrete mix, and then the mixed results were compared with standard concrete in the same mix composition. The research was conducted in the laboratory, namely through testing the compressive strength of concrete using a cube test object measuring 15 x 15 x 15 cm. Mixed concrete mix was made in 8 trials with the composition of rock waste 10%, 20%, 30%, 40%, 50%. The compressive strength test was carried out on the specimens at 28 days. From the analysis of the compressive strength data, concrete with the utilization of rock waste in the concrete mix has a compressive strength value that increases according to the proportion of rock powder waste. From the compressive strength test results, it meets the requirements as planned concrete, namely K225.